The police subculture and occupational socialization: Exploring individual and demographic characteristics - Britz, Marjie T. (American journal of criminal justice, 1997)
Popular in the law enforcement literature, the concept of the “police subculture” traditionally has been predicated on homogeneous personnel selections. Although female and minority representation has increased in law enforcement, the impact of females and minorities on the police subculture has not been empirically evaluated. Traditional research in this area has suggested that the socialization process is so intense and the subculture so strong that individual characteristics are quickly overwhelmed. However, these studies were undertaken prior to the mandated introduction of female and minority officers. Results of this study show no significant relationship exists between occupational identification and demographic characteristics; however, level of socialization does show a significant relationship to demographic variables. The sample consisted of four regularly scheduled academy classes with varying levels of police experience. This sample was selected due to the diversity in the level of police experience among respondents. It was hypothesized that demographic variables, such as race, gender, age, military experience and level of police experience, would not significantly affect occupational identification or levels of socialization. The data indicated that individual characteristics, such as race, gender, age, military experience, and level of police experience, did not appear to have a significant effect on occupational solidarity. These individual characteristics, however, were found to display significant relationships with level of socialization.